The Impact of Internationalization on Higher Education Institutions - Saira Khurram; Dr Javid Ahmed; Kamran Mujahid; Mamoona Anam; Tabassum Akhtar Hafiza (Social Science Review Archives, 2025)
This research paper reviewed the effect of internationalization on Pakistan higher education institutions using a mixed-method research design. The study was carried out in fifteen universities in Karachi, Lahore and Islamabad, which include 450 respondents using questionnaires and 25 stakeholders using interviews. The research was conducted into the impact of internationalization on the quality of the institutions, academic performance of the students, faculty and organizational capacity. The results have shown that internationalization had a great impact on the productivity of the research done, the quality of teaching as well as the international recognition of the Pakistani universities. Nevertheless, there were financial limitations, language barriers, and institutional capacity limitations. Research collaborations were more emphasized in public universities, whereas in private institutions more emphasis was made on a student exchange program. The research established positive relationships between internationalization practices and institutional ranking, graduate employability and research output. The qualitative study revealed essential success factors such as commitment of leadership, sufficient funding and agreements with foreign institutions. The study came to a conclusion that as much as internationalization holds significant positive effects to Pakistani institutions of higher education, successful execution of the process necessitates detailed planning, resource mobilization and enabling policy environments. These results can be used to make sense of internationalization processes in developing nations and can inform institutional leaders and policymakers in the higher education sector in Pakistan.